2015
DOI: 10.1007/s13594-015-0266-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the in vitro anti-atherogenic activities of goat milk and goat dairy products

Abstract: Given that goat milk and dairy products should be consumed daily according to suggestions based on Mediterranean diet, the current study evaluates the antiatherogenic properties of goat milk and goat dairy products (yogurt and white cheese). Total lipids (TLs) of all three samples were extracted by the method of Bligh and Dyer and further separated into total polar lipids (TPLs) and total neutral lipids (TNLs) by counter current distribution. The fatty acid profiles of TPL and TNL of all three samples were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 24 publications
4
24
0
Order By: Relevance
“…2a and b, seven bands of polar lipid fractions have been found in both yogurt samples. These results correspond with previously published research on the lipid fractions obtained in goat cheese (Poutzalis et al, 2016). …”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…2a and b, seven bands of polar lipid fractions have been found in both yogurt samples. These results correspond with previously published research on the lipid fractions obtained in goat cheese (Poutzalis et al, 2016). …”
Section: Resultssupporting
confidence: 93%
“…The TNL fraction of goat yogurt was found to exhibit statistically higher levels ( p < 0.05) of caprylic acid (C8:0), capric (10:0), lauric (12:0), myristic (14:0), palmitic (16:0), oleic (18:1), linoleic (18:2) and α-linolenic (18:3) fatty acids in contrast to the TNL fractions of ewe and cow yogurts (Table 3). The rather low levels of fatty acids in the TNL and TPL fractions are in concurrence with similar work on the TPL and TNL of goat dairy products (Poutzalis et al, 2016). …”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…In particular, Greek style yogurts produced with caprine and ovine milk have demonstrated greater PAF inhibitory properties in comparison to bovine yogurts. Research in relation to the anti-PAF activities of dairy products has demonstrated that the fermentation of milk to yogurt and then to cheese induces greater anti-thrombotic activity against PAF [11,12]. We focus on the effect of lipolysis and on the role of starter cultures such as Streptococcus thermophilus and Lactobacillus delbrueckii subsp.…”
Section: Ovine and Caprine Fermented Milk Productsmentioning
confidence: 99%